The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Poids - Carof, Solenne (Encyclopédie critique du genre, 2016)
Cette notice, en analysant comment le poids est à la fois le réceptacle de différentes normes et représentations sociales, mais également l’objet de revendications et de résistances, s’inscrit pleinement dans les thématiques des études sur le genre. Le poids permet, en effet, de saisir aussi bien les rapports sociaux révélés dans la prégnance de certaines normes corporelles - la minceur par exemple - que l’interdépendance de ces normes sociales avec d’autres rapports de domination. Être désigné comme « normal » ou « obèse », au-delà de l’historicité et des controverses entourant ces catégorisations, n’a pas le même sens selon les caractéristiques sociales des individus et peut reconfigurer les rapports sociaux existants.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; corps; cours; discipline; europe; france; grossophobie; inégalités; matérialité; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; violences

Introduction générale. Penser la violence des femmes : enjeux politiques et épistémologiques dans Penser la violence des femmes - Cardi, Coline; Pruvost, Geneviève (Penser la violence des femmes, 2012)
Tueuses, ogresses, sorcières, pédophiles, hystériques, criminelles, délinquantes, furies, terroristes, kamikazes, cheffes de gang, lécheuses de guillotine, soldates, policières, diablesses, révolutionnaires, harpies, émeutières, pétroleuses, viragos, guerrières, Amazones, boxeuses, génocidaires, maricides... Qu'y a-t-il de commun entre toutes ces figures ? Pour le comprendre, il importe d'exhumer, de dénaturaliser, d'historiciser et de politiser la violence des femmes. Telle est l'ambition de cet ouvrage qui propose une approche pluridisciplinaire sur un sujet trop longtemps ignoré des sciences sociales. Cette somme inédite, réunissant des études historiques, anthropologiques, sociologiques, linguistiques et littéraires, révèle combien la violence des femmes est au cœur d'enjeux d'ordre à la fois politique et épistémologique. Penser la violence des femmes, c'est en faire un véritable levier pour considérer autrement la différence des sexes, la violence et, par-delà, l'ordre social.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; occident; pol4022; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique; sciences humaines; thématiques; violences; épistémologie

Honor killings in the Middle East and North Africa: a systematic review of the literature - Kulczycki, Andrzej; Windle, Sarah (Violence against women, 2011)
A systematic review of the research literature on honor killings in the Middle East and North Africa (MENA) indicates a paucity of studies relative to the presumed magnitude of the problem. Forty articles were reviewed and critically appraised, of which only 9 contained primary data and 11 presented original secondary analyses. Despite a recent increase in published studies, persistent methodological limitations restrict the generalizability of findings. Most studies focus on legal aspects, determinants, and characteristics of victims and perpetrators. Victims are mostly young females murdered by their male kin. Unambiguous evidence of a decline in tolerance of honor killings remains elusive.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; cours; droits des femmes*; féminisme islamique; maghreb; moyen-orient; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sex2283; sexisme; systèmes d'oppressions; thématiques; violences

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Travail du sexe : tout ce que vous avez toujours voulu savoir, mais n'avez jamais osé demander - Mensah, Maria Nengeh; Lee, Cynthia (Service aux collectivités de l'UQAM/Stella, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; SAC; amériques; approches et analyses; femmes*; périodes historiques; québec; rapport; rapports sociaux de sexe; régions géographiques; thématiques; travail; travail du sexe; violences